2013
DOI: 10.1002/jmri.24406
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular reactivity mapping in patients with low grade gliomas undergoing presurgical sensorimotor mapping with BOLD fMRI

Abstract: Purpose i) to validate Blood Oxygenation Level Dependent (BOLD) breath hold cerebrovascular reactivity mapping (BH CVR) as an effective technique for potential detection of neurovascular uncoupling (NVU) in a cohort of patients with perirolandic low grade gliomas undergoing presurgical functional magnetic resonance imaging (fMRI) for sensorimotor mapping, and ii) to determine whether NVU potential, as assessed by BH CVR mapping, is prevalent in this tumor group. Materials and Methods We retrospectively evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(130 citation statements)
references
References 29 publications
9
114
2
5
Order By: Relevance
“…In both cases, these results were reflected in positive ASs for both resting-state and task-based fMRI maps. Absent or pathologically decreased task-based BOLD fMRI activation in the presence of a tumor or other resectable focal brain lesion, in the absence of a focal neurological deficit attributable to destruction of the eloquent cortical region that would be expected to produce a robust BOLD response, represents direct evidence of NVU (Hou et al, 2006;Ulmer et al, 2003;Zacà et al, 2014). Although some degree of asymmetry of task-based activation in the primary motor network has been reported in previous studies of normal volunteers (Dassonville et al, 1997;Jancke et al, 1998;Solodkin et al, 2001), the degree of asymmetry observed has been less substantial than what we observed in patients with gliomas, both in this small series and in prior publications that included larger patient series (Agarwal et al, 2015;Zacà et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases, these results were reflected in positive ASs for both resting-state and task-based fMRI maps. Absent or pathologically decreased task-based BOLD fMRI activation in the presence of a tumor or other resectable focal brain lesion, in the absence of a focal neurological deficit attributable to destruction of the eloquent cortical region that would be expected to produce a robust BOLD response, represents direct evidence of NVU (Hou et al, 2006;Ulmer et al, 2003;Zacà et al, 2014). Although some degree of asymmetry of task-based activation in the primary motor network has been reported in previous studies of normal volunteers (Dassonville et al, 1997;Jancke et al, 1998;Solodkin et al, 2001), the degree of asymmetry observed has been less substantial than what we observed in patients with gliomas, both in this small series and in prior publications that included larger patient series (Agarwal et al, 2015;Zacà et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon of neurovascular uncoupling (NVU) is an under-recognized, but critical, limitation of clinical fMRI (Holodny et al, 2000;Hou et al, 2006;Ulmer et al, 2003). Investigations relating to brain tumor-related NVU and its effects on fMRI have been performed to date with task-based fMRI only and at conventional MRI field strengths (3 Tesla and lower) (Holodny et al, 2000;Hou et al, 2006;Jiang et al 2010;Ulmer et al, 2003;Zacà et al, 2014). A previous study ) demonstrated brain tumor-related NVU through a combination of breath hold cerebrovascular reactivity (BH CVR) and task-based fMRI, while another publication (Agarwal et al, 2015) demonstrated tumor-related NVU in restingstate fMRI (rsfMRI).…”
mentioning
confidence: 99%
“…The prevalence of NVU in brain tumors is quite high according to recent series, [8][9][10] though the examples in these series suggest that NVU may not necessarily be an all-or-none (ie, binary) phenomenon, but rather may be present to variable degrees, resulting in variable degrees of reduction of expected ipsilesional BOLD activation in eloquent cortical regions and complete absence of detectable activation only in some cases. 10 Detection of such NVU potential is critical for adequate interpretation of clinical BOLD fMRI activation maps because false-negative activation may be present, depending on the statistical thresholding used. Similar NVU can be seen in AVMs due to regional hemodynamic abnormalities related to the exhaustion of vascular reserve secondary to arteriovenous shunting and loss of perfusion pressure or venous congestion with high outflow resistance.…”
Section: Abbreviationsmentioning
confidence: 99%
“…[8][9][10] In the case of low-grade gliomas, the exact mechanism responsible for the NVU is not clear but may be associated with astrocytic dysfunction related to the infiltrative tumors. The prevalence of NVU in brain tumors is quite high according to recent series, [8][9][10] though the examples in these series suggest that NVU may not necessarily be an all-or-none (ie, binary) phenomenon, but rather may be present to variable degrees, resulting in variable degrees of reduction of expected ipsilesional BOLD activation in eloquent cortical regions and complete absence of detectable activation only in some cases. 10 Detection of such NVU potential is critical for adequate interpretation of clinical BOLD fMRI activation maps because false-negative activation may be present, depending on the statistical thresholding used.…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation